Redefining inclusivity: A cultural studies perspective through systematic literature review - Deny Gunawan Susandi; Dadi Waras Suhardjono; Erma Damayanti; Artipah Artipah; Ditta Mustika Rakhmawati (Universitas Pakuan, 2025)
This research focuses on the wide-ranging notion of inclusivity looking at cultural studies and highlights the non-Western contexts like Indonesia. Following PRISMA protocols, a systematic literature review was carried out on 45 selected articles published between the years of 2015 and 2025. The findings show that there are three primary themes: culture representation, power relations, and local traditions. It can also be remarked that the western notion of inclusivity seems inadequate when placed in collectivist contexts. ‘Gotong royong’ as an example of Indonesian inclusivity models reflects traditional local customs. Furthermore, decolonial and intersectional frameworks illuminate the enduring socio-historical inequalities that are shaped through identity-based hierarchies within practices of inclusion. This research articulates the need to develop a culturally specific framework of inclusivity which regards inclusivity as multiscopic; rooted in local contexts while applicable worldwide. It seeks to contribute to scholarship and guide policy for more inclusive governance towards social justice.